Os efeitos da ação antrópica sobre a distribuição de macroinvertebrados no Rio Guareí, São Paulo - Fulan, Joao Anderson; Henry, Raoul; Davanso, Rosemary (My University, 2012)
In this study, it was examined, during the period from March to December 2006, the effects of human disturbance on themacroinvertebrates that live near macrophytes in Guare River, São Paulo State - Brazil. It was questioned if the high conductivityrecorded in Guare River affected the distribution of the macroinvertebrates and what were the most important variables thataffect macroinvertebrates in a river with a strong nutrient concentration. The objective of this study was to investigate theeffects of environmental variables on densities and composition of the macroinvertebrates. Three stands of aquatic plantswere sampled with with 0.25 mm mesh net on a 0.07 m2 square metal frame. Air and water temperature, depth, pH, electricalconductivity, suspended solids, dissolved oxygen and macrophyte biomass were measured. A canonical correspondence analysis(CCA) was performed using the density of the macroinvertebrates and environmental variables. Chironomidae, Culicidae,Acanthagrion, Coryphaeschna, Erythrodiplax, Miathyria marcella, Micrathyria, Gastropoda, Ostracoda and Hemiptera werethe only taxa that showed significant correlation with the axes. From the results, we can conclude that the high conductivity recordedin Guare River due to the high amount of organic matter released during its course did not significantly affected thedistribution of the macroinvertebrates during the studied period. However, the ACC recorded that oxygen was the most significantenvironmental factor for the density variance of the macroinvertebrates, especially larval Odonata.
Anthropic action influence on macroinvertebrates distribution in Guarei River, São Paulo State - Brazil.